An Evaluation of Educational Environment Across The Phases of MBBS Course in Non-Government And Government Medical Colleges in Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Medical education has evolved from teacher-centered to student-centered models, yet the undergraduate curriculum in Bangladesh remains traditional. Acknowledging the pivotal role of educational environment in shaping effective curriculum, educators strive to foster student-friendly environment while maintaining educational quality. This study compares students' perceptions of educational environments in government and non-government medical colleges across MBBS phases, aiming to provide insights into quality of educational environment in both sectors.Materials and methods: This cross-sectional study included 400 MBBS students from 4 government and nongovernment institutions. Within each institution, 25 students were selected from each phase of MBBS course. SPSS software was used to analyze the data and independent t-test compared scores between both groups, with significance set at 'p' < 0.05.  Results: Non-government students scored higher across all MBBS phases, with significant differences in phase 1 (DREEM score-p 0.00, SPL-p 0.00 and SPA-p 0.00), and phase 3 (SPL- p 0.04, SSSP- p 0.04). No significant differences were observed in phases 2 and 4.Conclusion: Students in non-government medical colleges perceive educational environment more positively than government counterparts across all phases of MBBS course, necessitating targeted interventions for improvement.JCMCTA 2024 ; 35 (1) : 71-76